Inside Back Cover: Photocatalytic Formic Acid Conversion on CdS Nanocrystals with Controllable Selectivity for H2 or CO (Angew. Chem. Int. Ed. 33/2015). Issue 33 (17th July 2015) - Kuehnel, Moritz F.; Wakerley, David W.; Orchard, Katherine L.; Reisner, Erwin
<x xml:space="preserve">Abstract</x> The bifunctionality of CdS quantum dots for the light‐driven conversion of formic acid into gaseous fuels is demonstrated by E. Reisner et al. in their Communication on page 9627 ff. Depending on the conditions and particle surface groups, irradiated CdS nanocrystals produce hydrogen and carbon dioxide through dehydrogenation of formic acid or carbon monoxide and water through dehydration. Hydrogen evolution occurs at an unprecedented rate compared to analogous systems, and this process establishes formic acid as a material for carbon monoxide storage.